2021
DOI: 10.21203/rs.3.rs-614743/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanisms Involved in the Anti-Tumor Effects of Toosendanin in Glioma Cells

Abstract: Background: Toosendanin (TSN) is a triterpenoid compound mainly used as an ascaris repellant. Recent studies have shown that it possesses antitumor effects in many types of tumor cells. However, the effects of TSN on glioma cells have rarely been reported. Methods: Different assays were performed to investigate the effects of TSN on the different glioma cell lines including U87MG and LN18. The assays included colony formation, wound healing, and transwell assays. Furthermore, Hoechst 3342 staining, flow cytome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…such as colorectal cancer cells and glioma cells (22)(23)(24)(25). Our previous studies demonstrated that TSN induces apoptosis of human gastric cancer MKN45 cells (26) and induces formation of CTPS cytoophidia.…”
Section: Ctps Cytoophidia Formation Affects Cell Cycle Progression An...mentioning
confidence: 99%
“…such as colorectal cancer cells and glioma cells (22)(23)(24)(25). Our previous studies demonstrated that TSN induces apoptosis of human gastric cancer MKN45 cells (26) and induces formation of CTPS cytoophidia.…”
Section: Ctps Cytoophidia Formation Affects Cell Cycle Progression An...mentioning
confidence: 99%
“…Next, the effect of compound 4a 7 on HeLa cells colony formation was explored to further illustrate the antiproliferative activity [26] . As shown in Figure 3, compared to the control, compound 4a 7 can significantly reduce the formation of HeLa cell colonies in a concentration‐dependent manner.…”
Section: Resultsmentioning
confidence: 99%